A method for digesting fluorine-containing aluminum inorganic material and a method for detecting aluminum content thereof
By employing layered packing, stepped heating, and boric acid complexation, the problems of sample loss and instrument corrosion in aluminum fluoride detection have been solved, achieving efficient and accurate aluminum content detection. This method is applicable to electrolytic aluminum, ceramics, and new energy fields.
Patent Information
- Application Number
- CN202611540880.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-30
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies for detecting aluminum content in aluminum fluoride suffer from problems such as low detection efficiency, large human error, inaccurate results, and poor reproducibility. Furthermore, the alkali fusion method is subject to problems such as sample splashing, sintering, aluminum element loss, and fluoride ion corrosion of the instrument.
A layered filling and stepped heating alkaline melting method is adopted, combined with acidification to adjust the pH to 2-3 and boric acid complexation reaction, to form a stable aluminum ion form and mask free fluoride ions. With the addition of graded dilution and characteristic spectral line detection, a complete chemical regulation closed loop is formed.
It achieves high precision and high reproducibility in aluminum content detection, reduces reliance on operator experience, improves detection efficiency and accuracy, and is suitable for industrial batch testing.
Smart Images

Figure CN123028874A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of analytical chemistry technology, and specifically relates to a digestion method for fluorine-containing aluminum inorganic materials and a method for detecting their aluminum content. Background Technology
[0002] Aluminum fluoride is a core raw material in the electrolytic aluminum industry, ceramics, metallurgy and new energy fields. Aluminum content is a key indicator for determining product grade and controlling production process. The industry has high requirements for its detection accuracy, repeatability and efficiency.
[0003] Currently, the standard method for determining the aluminum content in cryolite and aluminum fluoride is the EDTA volumetric method (as specified in YS / T 273.4-2006 "Chemical Analysis Methods and Physical Property Determination Methods for Cryolite" and YS / T 581.4-2006 "Chemical Analysis Methods and Physical Property Determination Methods for Aluminum Fluoride"). Traditional EDTA chemical titration has low equipment investment, but the pretreatment process is lengthy, requiring multiple pH adjustments, impurity masking, and indicator determination of the titration endpoint. This involves significant human intervention, with the titration endpoint relying on subjective judgment, leading to large human errors, low detection efficiency, significant parallel sample deviation, and a limited number of samples that can be tested per day, making it unsuitable for the growing demand for industrial batch testing.
[0004] Another approach uses alkaline melting pretreatment combined with inductively coupled plasma optical emission spectrometry (ICP-OES) to detect aluminum content. This existing approach has the following core drawbacks: First, simply mixing sodium hydroxide directly with the sample followed by a one-time heating and calcination without a stepped temperature control step leads to rapid heating, which can cause splashing, localized sintering, crucible adhesion, and incomplete material decomposition. Aluminum elements are trapped in the solid phase, resulting in a systematically low detection result. Second, the resulting strongly alkaline leachate allows aluminum ions to easily form flocculent aluminum hydroxide precipitates under alkaline conditions, causing loss of the analyte. Simultaneously, the high concentration of sodium salt creates a strong matrix effect, suppressing aluminum spectral lines. The existing technology suffers from several drawbacks. First, it lacks strength and precision in detection. Second, the decomposition of fluorinated aluminum materials releases a large amount of free fluoride ions. These fluoride ions form fluorine-aluminum complexes with aluminum ions, altering the aluminum element signal response and causing quantitative distortion. Third, free fluoride ions are highly corrosive and can easily damage instrument components such as ICP injection lines and nebulizers. Fourth, the existing technology does not systematically define key process parameters such as flux loading methods, step-heating parameters, leaching conditions, acidification pH, boric acid addition, dilution ratios, analytical spectral lines, and standard curve concentration points. This results in significant dispersion of results for different operators and different batches, indicating a low degree of method standardization.
[0005] Therefore, there is an urgent need in this field for a digestion method for fluorine-containing aluminum inorganic materials and a method for detecting their aluminum content. A complete solution integrating step-heating melting process optimization, acidity control, efficient fluoride ion masking, standardized graded dilution, and dedicated analytical spectra and standard curves is needed to fully eliminate various interfering factors while leveraging the strong digestion ability of sodium hydroxide. Summary of the Invention
[0006] This invention provides a method for digesting fluorinated aluminum inorganic materials and a method for detecting their aluminum content. The technical problem to be solved is that in the high alkalinity and high salinity system formed by the alkaline fusion digestion of fluorinated aluminum materials with sodium hydroxide, free fluoride ions, aluminum ions, and protons (pH) are in a coupled equilibrium state. On the one hand, free fluoride ions chelate with the aluminum ions being measured to form a series of fluorinated aluminum complexes (AlF). 2+ AlF2 + AlF3, AlF6 3- Fluoride ion complexation interference, aluminum ion hydrolysis loss, and instrument corrosion risk are all unique technical challenges in the alkaline fusion-ICP-OES detection of fluoride-containing aluminum materials. These interferences directly alter the spectral response of aluminum and cause quantitative distortion. Furthermore, the alkaline environment is highly corrosive to the ICP injection system. Simultaneously, the strong alkaline environment causes aluminum ions to hydrolyze, forming flocculent aluminum hydroxide precipitates, further leading to the loss of the analyte. These three types of interference cannot be eliminated by a single reagent or parameter. How to simultaneously eliminate fluoride ion complexation interference, aluminum ion hydrolysis loss, and instrument corrosion risk in the same digestion solution is a unique technical challenge in the alkaline fusion-ICP-OES detection of fluoride-containing aluminum materials. This also requires addressing issues such as sample splashing, sintering adhesion to the walls, and incomplete digestion during the alkaline fusion process of fluoride-containing aluminum materials.
[0007] A method for digesting fluorine-containing aluminum inorganic materials includes the following steps: (1) Sample pretreatment: The fluorinated aluminum inorganic material is dried to constant weight and cooled for later use; the fluorinated aluminum inorganic material is aluminum fluoride, cryolite, potassium fluoroaluminate or a mixture thereof; (2) Layered filling: Solid sodium hydroxide is laid at the bottom of the nickel crucible. The fluorinated aluminum inorganic material dried in step (1) is weighed and laid flat on top of the bottom layer of sodium hydroxide. The surface of the fluorinated aluminum inorganic material is covered with solid sodium hydroxide. The sodium hydroxide at the bottom of the nickel crucible accounts for 55% to 65% of the total sodium hydroxide mass. The total sodium hydroxide is the sum of the sodium hydroxide at the bottom of the nickel crucible and the sodium hydroxide covering the surface of the fluorinated aluminum inorganic material. The mass ratio of the fluorinated aluminum inorganic material to the total sodium hydroxide is 1:40 to 60. (3) Step heating and calcination: Place the filled nickel crucible into a muffle furnace, first heat it to 180~220℃ and calcinate it at a constant temperature for 8~12 minutes, then heat it to 530~570℃ and calcinate it at a constant temperature for 45~55 minutes; (4) Cooling leaching: After the calcination is completed, remove the nickel crucible and let it cool naturally to room temperature. Add hot water at 60~80℃ into the crucible and heat and stir at 80~100℃ until the melt is completely dissolved. (5) Acidification and fluorine masking: After the leaching and dissolution are completed, the solution is cooled to room temperature. First, hydrochloric acid or nitric acid is added dropwise to adjust the pH to 2-3. Then, boric acid is added to the solution so that the boric acid complexes the free fluoride ions released during the digestion of the fluorine-containing aluminum inorganic material under the pH conditions to obtain a digestion solution. The digestion is then completed. The amount of boric acid added is 4-6g per 0.1g of the fluorine-containing aluminum inorganic material.
[0008] Further, in step (1), the drying conditions are drying at 100~110℃ to constant weight; in step (4), the mixture is heated and stirred on a hot plate at 80~100℃ until the molten material is completely dissolved.
[0009] Further, in step (2), the sodium hydroxide at the bottom of the nickel crucible accounts for 55% to 65% of the total sodium hydroxide mass, and the total sodium hydroxide is the sum of the sodium hydroxide at the bottom of the nickel crucible and the sodium hydroxide covering the surface of the fluorine-containing aluminum inorganic material; the mass ratio of the fluorine-containing aluminum inorganic material to the total sodium hydroxide in step (2) is 1:40 to 60.
[0010] Further, the stepped heating and calcination in step (3) involves heating to 200°C and calcining at a constant temperature for 10 minutes, then heating to 550°C and calcining at a constant temperature for 50 minutes.
[0011] Further, the acid mentioned in step (5) is hydrochloric acid or nitric acid; the amount of boric acid added in step (5) is 4~6g of boric acid added per 0.1g of the fluorinated aluminum inorganic material.
[0012] This invention also provides a method for detecting the aluminum content in fluorinated aluminum inorganic materials, comprising the digestion method described above, and further comprising the following steps: Step 1, First volume adjustment: Transfer all the digestion solution to the first volumetric flask, and make up to volume with pure water to obtain the first-stage mother liquor; Step 2, fractional dilution: Take the second volumetric flask and pre-add acid to it, then transfer the first-stage mother liquor into it and dilute to the mark to obtain the test solution; Step 3: Preparation of standard curve: Using the matrix matching method, a sodium salt solution with a sodium ion concentration equivalent to that of the test solution is used as the matrix. The aluminum standard stock solution is diluted to prepare the aluminum standard working solution. The aluminum element characteristic emission line at 396.1 nm is selected for detection using an inductively coupled plasma optical emission spectrometer (ICP-OES). The standard curve is plotted with the aluminum element concentration as the abscissa and the spectral line intensity as the ordinate. Step 4, Sample Testing: Under the same instrument parameters and spectral analysis conditions as in Step 3, determine the intensity of the aluminum spectral line in the test solution, substitute it into the standard curve to calculate the concentration of aluminum in the test solution; combine the sample weight and the total dilution factor of the two stages to calculate the mass percentage of aluminum in the fluorine-containing aluminum inorganic material.
[0013] Furthermore, in step one, the first volumetric flask is a 500mL volumetric flask; in step two, the second volumetric flask is a 100mL volumetric flask, and the pre-added acid is 0.5~2mL of hydrochloric acid or nitric acid.
[0014] Furthermore, in step two, the volume of the primary mother liquor transferred is 0.5~2mL, and the ratio of the volume of pre-added hydrochloric acid or nitric acid to the volume of the primary mother liquor transferred is 1:1.
[0015] Furthermore, the aluminum concentration gradient of the aluminum standard working solution in step three is 0 μg / mL, 0.2 μg / mL, 0.8 μg / mL, and 1.4 μg / mL.
[0016] The inventive concept of this invention lies in the following: For the special system of "fluorine-aluminum-pH" ternary coupling equilibrium in the alkaline fusion digestion solution of fluorinated aluminum materials, a stepwise chemical control method is adopted—first, the strong alkaline leaching solution is precisely adjusted to pH 2-3 with acid, under which aluminum ions exist in a stable Al³⁺ state. + It exists in its original form and does not undergo hydrolysis; then, under the same pH conditions, boric acid is added, utilizing the reaction of boric acid with fluoride ions to form fluoroborate ( ). The complexation reaction of (etc.) will transfer free fluoride ions from "al with Al" 3+ The fluoride is quantitatively transferred out in the equilibrium of "competitive complexation". The above-mentioned sequence of steps, "first fix the pH, then complex and mask the fluoride", creates a synergistic effect between pH and boric acid: pH 2-3 is not only a prerequisite for establishing a stable form of aluminum ions, but also the acidity condition under which the boric acid-fluoride complexation reaction can proceed efficiently with low loss of free hydrofluoric acid volatilization; conversely, boric acid complexation eliminates the signal interference of fluoride ions that may be released again with pH fluctuations on aluminum. The two complement each other and are indispensable, forming a complete chemical regulation closed loop for fluoride-containing systems.
[0017] The principle and function of parameter setting in the above key steps of this invention are as follows: In step (1), drying to constant weight means that the mass difference between two consecutive drying cycles is no more than 0.0002 g. 100~110℃ is the conventional temperature for removing adsorbed water from inorganic samples, which can completely remove free water from the sample surface. Moreover, this temperature is much lower than the decomposition temperature of fluorinated aluminum materials, so it will not cause thermal decomposition of the sample or loss of components. If the sample is not dried or the drying temperature is insufficient, the moisture will increase the apparent mass of the sample, resulting in a lower effective mass and a lower final test result. At the same time, the moisture will rapidly vaporize during the high-temperature burning stage, which can easily cause sample particles to splash, leading to loss of the analyte and increasing the deviation of parallel samples.
[0018] In step (2), a three-layer structure is adopted. Sodium hydroxide is a strong alkaline flux, and its core function is to destroy the dense lattice of fluorine-containing aluminum materials at high temperature, converting insoluble fluorides and aluminum compounds into soluble salts. The bottom of the muffle furnace crucible has the highest temperature. The thick layer of flux at the bottom can isolate the sample from the high-temperature crucible wall, avoiding local overheating and crucible sticking. The upper layer of flux completely seals the sample surface, isolates the airflow in the furnace, and prevents sample powder from splashing and trace amounts of fluoride from volatilizing at high temperature. The bottom flux accounts for a higher proportion than the upper layer, which prioritizes solving the problem of high-temperature surface sticking. The upper flux provides sealing protection, which is the optimal combination of isolation, heat conduction, and anti-vaporization. The flux-sample ratio of 40:1 to 60:1 is the optimal balance point: when the flux-sample ratio is lower than 40:1, the total amount of flux is insufficient and cannot completely wet and coat the sample, and it is easy to form sintered hard blocks after melting; when the flux-sample ratio is higher than 60:1, the sodium salt concentration in the system is too high, resulting in a strong matrix effect.
[0019] In step (3), the low-temperature stage of 180~220℃ for 8~12min gradually removes residual moisture from the sample and flux, preventing rapid vaporization of moisture from causing sample splashing. Simultaneously, it allows the flux and sample to be slowly heated, removing residual moisture and ensuring uniform heating, laying the foundation for the subsequent high-temperature reaction. The high-temperature stage of 530~570℃ for 45~55min keeps sodium hydroxide in a molten state, exhibiting good reactivity and fully disrupting the crystal lattice of the fluorinated aluminum material. The longer holding time ensures complete solid-liquid reaction, achieving thorough sample decomposition. This temperature range effectively controls fluoride volatilization and reduces the corrosion rate of the nickel crucible by strong alkali.
[0020] In step (4), adding water directly to the high-temperature crucible can easily cause cracking and damage due to thermal expansion and contraction. Natural cooling can protect the nickel crucible and allow the molten material to cool down slowly, reducing the risk of splashing. Using hot water at 60~80℃ can improve the dissolution efficiency and accelerate the dissociation of molten salt; heating and stirring can enhance the mass transfer effect and ensure that the molten product is completely dissolved.
[0021] In step (5), after the alkaline fusion decomposition and leaching are completed in steps (2) to (4), aluminum in the leaching solution exists in the form of aluminate and other forms, and free fluoride ions exist in the form of F. - The / HF form exists in large quantities. This method does not employ simple "neutralization to near neutrality" or "one-time excessive acidification," but instead first fixes the system at pH 2-3. This acidity has a dual deterministic effect: firstly, aluminum ions exist stably as Al³⁺ within this pH range. + It exists in a simple ionic form and thermodynamically does not form aluminum hydroxide precipitate, thus completely eliminating aluminum hydrolysis loss; secondly, at this acidity, fluorine exists as HF molecules and reacts with F. - The coexisting form distribution avoids both the large-scale volatilization loss of hydrofluoric acid under strong acid conditions and the loss of F under weak acid conditions. -The high free fluoride concentration creates an optimal acidity window for subsequent boric acid complexation. The added boric acid then complexes with the free fluoride to form stable fluoroborate, effectively dissociating the fluoride ions from their coordination equilibrium with aluminum ions.
[0022] In the detection method, step one uses a fixed-volume volumetric flask to make up the volume, which can unify the sodium salt matrix and total ion concentration of all samples, blanks, and quality control samples, and eliminate pretreatment volume errors.
[0023] Step two involves graded dilution, which significantly reduces the concentration of aluminum ions and the sodium salt matrix, adapting to the linear detection range of ICP-OES and avoiding problems such as excessive concentration and salt accumulation. Pre-acidification can maintain the pH of the system in the acidic range, inhibiting the hydrolysis of aluminum ions throughout the process, ensuring the stability of the aluminum ion form in the test solution, and at the same time unifying the acidity of all test solutions to eliminate matrix interference caused by acidity fluctuations.
[0024] In step three, the characteristic emission line of aluminum at 396.1 nm was selected for detection. The 396.1 nm aluminum spectral line exhibits high sensitivity and a strong response signal. In this high-salt, fluorine-containing matrix, it experiences minimal spectral interference, maintains a stable baseline, and demonstrates superior detection stability compared to other aluminum spectral lines, making it suitable for batch sample detection using this method. A series of aluminum standard working solutions were prepared with concentrations of 0 μg / mL, 0.2 μg / mL, 0.8 μg / mL, and 1.4 μg / mL, respectively. This concentration gradient covers the actual concentration range of the analyte, with uniform gradient intervals and reasonable settings for zero, low, medium, and high concentration points, ensuring good curve linearity and enabling accurate interpolation and quantification of the analyte. Simultaneously, a matrix-matched method was used to prepare the standard solutions, eliminating matrix effects.
[0025] Step 4: Under identical instrument parameters and spectral analysis conditions, determine the intensity of the aluminum element spectral line in the test solution, substitute it into the standard curve regression equation, and calculate the aluminum concentration in the test solution; combine the sample weight and the total dilution factor of the two stages to calculate the mass percentage of aluminum in the fluorine-containing aluminum inorganic material.
[0026] The process parameters, material ratios, temperature programs, time, volume, and operation sequences of this invention are all designed based on the physicochemical properties of fluorine-containing aluminum inorganic materials, the melting reaction mechanism of sodium hydroxide, the hydrolysis characteristics of aluminum ions, the interference mechanism of fluorine ions, and the detection requirements of ICP-OES instruments. Each process works together to form a closed loop.
[0027] Compared with the prior art, the present invention has the following technical effects: 1. To address the unique "fluorine-aluminum complexation interference" of fluorinated aluminum materials, this method employs a two-step chemical regulation process: "pH 2-3 acidification + boric acid complexation." This simultaneously achieves aluminum ion stabilization and free fluorine masking in the same digestion solution. When pH 2-3 is set alone without boric acid masking, fluorine-aluminum complexes can still form, resulting in a spiked recovery of only 90.4% and a relative standard deviation (RSD) of 1.64% (Comparative Example 5). Without pH control and boric acid masking, and with the system near neutral, aluminum hydrolysis and fluorine interference occur simultaneously, reducing the spiked recovery to 87.6% and the RSD to 1.89% (Comparative Example 4). Only by implementing both steps synergistically can the spiked recovery reach 98.6% and the RSD decrease to 0.62% (Example 1). These data were obtained under the premise of the same system, the same sample, and only the chemical regulation method was changed, directly demonstrating that the synergistic effect of "fixed pH + boric acid fluorine masking" is crucial and cannot be replaced by a single measure.
[0028] 2. This method converges the entire process of aluminum content detection into a fixed chemical condition window (the alkali fusion parameters, pH window, boric acid amount, dilution step, analytical spectral lines and standard curve gradients are all clearly defined), freeing the detection of fluorine-containing systems from dependence on operator experience (the original method had RSD > 3.0%), reflecting the systematic closed-loop characteristics of the method.
[0029] 3. This invention establishes a standardized process throughout the entire process, clearly specifying everything from the stepped heating and calcination parameters, cooling and leaching conditions, acidification and masking steps to the two-stage dilution system and instrument detection conditions. This significantly improves the reproducibility of the method, with a relative standard deviation (RSD) of ≤0.70% for six parallel sample determinations, which is far superior to the existing technology with an RSD >3.0%.
[0030] 4. This invention preferably uses the 396.1nm characteristic spectral line of aluminum, which has high sensitivity and low spectral interference; the concentration range of the gradient standard curve is highly matched with the test solution, and the standard curve is plotted using the matrix matching method, which effectively eliminates the matrix effect and achieves high quantitative accuracy.
[0031] 5. The two-stage gradient dilution design of this invention is reasonable, which greatly reduces the salinity and ion concentration of the test solution, effectively avoids salt accumulation in the ICP torch and nebulizer, adapts to the optimal detection range of the instrument, and has strong detection stability.
[0032] 6. The sodium hydroxide used in this invention has low procurement costs and can be used with conventional nickel crucibles, resulting in low overall consumable costs. It is easy to implement and popularize in industrial applications, and the entire process is suitable for batch testing in laboratories, with high overall efficiency. Attached Figure Description
[0033] Figure 1 This is a flowchart of the digestion method for the fluorine-containing aluminum inorganic material described in this invention; Figure 2This is a flowchart of the method for detecting the aluminum content in fluorinated aluminum inorganic materials according to the present invention; Figure 3 This is the standard curve graph of Example 1; where the solid line is the regression standard curve and the dots are the measured spectral intensity values of the standard working solutions at each concentration. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to specific embodiments of this application and the accompanying drawings. It should be noted that the following embodiments are examples of this invention and are only used to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of this invention can be made without departing from the spirit or scope of this invention.
[0035] Unless otherwise specified, all chemical reagents used in this invention are commercially available analytical grade reagents.
[0036] Example 1 This embodiment provides a digestion method for fluorinated aluminum inorganic materials and a method for detecting their aluminum content. The fluorinated aluminum inorganic material is aluminum fluoride.
[0037] 1. Digestion method: (1) Sample pretreatment: Take aluminum fluoride sample and place it in an oven. Dry it at 105℃ to constant weight. After taking it out, put it in a desiccator to cool to room temperature and seal it for later use. (2) Layered filling: Select a 50mL nickel crucible, evenly spread 3.0g of solid sodium hydroxide at the bottom of the crucible, accurately weigh 0.1000g of dried aluminum fluoride sample and spread it on top of the bottom flux, and evenly cover the sample surface with 2.0g of solid sodium hydroxide (the bottom sodium hydroxide accounts for 60% of the total sodium hydroxide mass, and the mass ratio of the sample to the total sodium hydroxide is 1:50). (3) Step heating and calcination: Place the filled nickel crucible into a muffle furnace, heat it to 200°C, calcinate it at a constant temperature for 10 minutes, and then continue to heat it to 550°C and calcinate it at a constant temperature for 50 minutes. (4) Cooling and leaching: After the calcination is completed, remove the nickel crucible and let it cool naturally to room temperature. Add about 30 mL of hot water at 60~80℃ to the crucible and place it on a hot plate to heat to 95℃. Stir until the melt completely disintegrates and dissolves. (5) Acidification of fluoride: After cooling the solution to room temperature, slowly add about 10 mL of concentrated hydrochloric acid, stir to neutralize excess sodium hydroxide, test with pH paper, adjust the pH of the solution to 2-3, add about 5 g of boric acid to the acidified solution, stir (heat if necessary) until completely dissolved, all free fluoride ions in the complexation system are combined, and the digestion is completed.
[0038] 2. Detection of aluminum content in samples: Instruments and operating conditions: Inductively coupled plasma optical emission spectrometer (ICP-OES), RF power 1300W, cooling gas (argon) flow rate 15L / min, auxiliary gas (argon) flow rate 0.3L / min, carrier gas (argon) flow rate 0.8L / min, observation mode is axial observation, and the spectral line to be analyzed is the characteristic emission line of aluminum at 396.1nm; Step 1, First volume adjustment: Transfer all the digestion solution to a 500mL volumetric flask, wash the crucible several times with pure water and combine the washing solutions, add pure water to adjust the volume to the mark, shake well, and obtain the first-stage mother liquor; Step 2, fractional dilution: Take a 100mL volumetric flask, add 1mL hydrochloric acid, use a pipette to transfer 1mL of the primary stock solution into it, add pure water to make up to the 100mL mark, shake well, and obtain the test solution; Step 3: Preparation of Standard Curve: Using the matrix matching method, a sodium salt solution with a sodium ion concentration equivalent to that of the test solution was used as the matrix. The aluminum standard stock solution was diluted to prepare the aluminum standard working solution. An inductively coupled plasma atomic emission spectrometer was used to detect the characteristic emission line of aluminum at 396.1 nm. A standard curve was plotted with aluminum concentration on the x-axis and spectral intensity on the y-axis (see attached diagram). Figure 3 The standard curve regression equation is: signal intensity (cps) = 566.490 × concentration (μg / mL) + 22.922, R² = 0.99915; Step 4: Sample testing: Measure the test solution under the same conditions, substitute the solution into the standard curve to calculate the concentration of aluminum in the test solution; combine the sample weight and the total dilution factor of the two stages to calculate the mass percentage of aluminum in aluminum fluoride.
[0039] Test results:
[0040] The results showed that the RSD of the six parallel determinations in this embodiment was 0.62%, and the spiked recovery rate was 98.6%. The RSD and spiked recovery rate indicate that the precision and accuracy are significantly better than those of the prior art.
[0041] Example 2 This embodiment provides a method for detecting the aluminum content in cryolite. The difference from Embodiment 1 is that the fluorine-containing aluminum inorganic material is cryolite, while the remaining steps are the same as in Embodiment 1.
[0042] Test results:
[0043] The RSD of six parallel determinations in this embodiment was 0.49%, and the spiked recovery rate was 96.8%. This method is applicable to fluorinated aluminum inorganic materials such as cryolite. The layered packing + stepped heating alkali fusion system can fully decompose cryolite, and boric acid effectively masks free fluoride ions. The aluminum element determination has excellent precision and accuracy, indicating that this detection method has good versatility for different fluorinated aluminum samples.
[0044] Example 3 This embodiment examines the digestion effect within different process parameter ranges. The difference from Example 1 is as follows: in step (2), the total amount of sodium hydroxide used is 4.0g (2.4g at the bottom and 1.6g at the top, with a mass ratio of aluminum fluoride to total sodium hydroxide of 1:40); in step (3), the low temperature section is kept at 180℃ for 12min, and the high temperature section is kept at 530℃ for 55min; in step (5), 4g of boric acid is added to complex free fluoride ions; the remaining steps are the same as in Example 1.
[0045] Test results:
[0046] The RSD of six parallel determinations in this example was 0.84%, and the spiked recovery rate was 95.7%. Within this parameter range, the alkali fusion reaction was sufficient, the amount of boric acid was adequate for fluoride ion masking, and the detection results were stable and accurate. Compared with Example 1, the reduced alkali dosage and slightly lower temperature resulted in a slight decrease in performance, indicating that the method remains stable and feasible within this parameter range. However, the reduction in alkali dosage and temperature slightly affects the digestion efficiency.
[0047] Example 4 This embodiment examines the digestion effect within different process parameter ranges. The difference from Example 1 is as follows: in step (2), the total amount of sodium hydroxide used is 6.0g (3.6g at the bottom and 2.4g at the top, with a mass ratio of aluminum fluoride to total sodium hydroxide of 1:60); in step (3), the low temperature section is kept at 220℃ for 8min and the high temperature section is kept at 570℃ for 45min; in step (5), 6g of boric acid is added to complex free fluoride ions; the remaining steps are the same as in Example 1.
[0048] Test results:
[0049] Testing showed that the RSD of six parallel determinations in this example was 0.77%, and the spiked recovery rate was 96.4%. Increasing the alkali dosage, raising the high-temperature section temperature, and shortening the holding time still achieved complete digestion of aluminum fluoride and sufficient boric acid complexation of fluoride ions, maintaining high precision and accuracy, demonstrating that this method has a wide tolerance window for process parameters.
[0050] Comparative Example 1 In this comparative digestion method, there is no layered loading step and the mixture is directly mixed. The difference from Example 1 is that in step (2), 0.1000g of aluminum fluoride sample and 5.0g of solid sodium hydroxide are directly mixed evenly and then loaded into a nickel crucible; the remaining steps are the same as in Example 1.
[0051] Test results:
[0052] The results showed that the RSD of the six parallel determinations in this comparative example was 9.31%, and the spiked recovery rate was 81.2%. Eliminating the layered packing method and directly mixing the sample with the flux led to localized sintering and splashing during the melting process, incomplete decomposition of some samples, lower test results, increased dispersion, and decreased accuracy. This demonstrates that layered packing is a necessary condition for ensuring stable test results.
[0053] Comparative Example 2 The comparative digestion method in this example does not involve stepwise heating. The difference from Example 1 is that in step (3), the muffle furnace is directly heated to 550°C and burned for 50 minutes; the remaining steps are the same as in Example 1.
[0054] Test results:
[0055] The RSD of the six parallel determinations in this comparative example was 3.12%, and the spiked recovery rate was 87.6%. Direct high-temperature ignition, with its rapid melting and intense exothermic reaction of sodium hydroxide, easily caused sample splashing and loss, resulting in poor sample decomposition consistency, increased parallel sample deviation, and overall lower results. This demonstrates that step-heating ignition can avoid sample splashing and ensure complete digestion.
[0056] Comparative Example 3 The comparative digestion method does not involve layered loading or stepped heating. The difference from Example 1 is that in step (2), 0.1000g of aluminum fluoride sample and 5.0g of solid sodium hydroxide are directly mixed evenly and then loaded into a nickel crucible; in step (3), the muffle furnace is directly heated to 550℃ and calcined for 50min; the remaining steps are the same as in Example 1.
[0057] Test results:
[0058] The comparative example showed an RSD of 6.64% and a recovery rate of 82.4% in six parallel determinations. Direct mixing of the sample with the solid alkali and rapid, one-time heating to a high temperature resulted in violent foaming during the melting reaction, easily leading to sample splashing and loss. Uneven contact between the sample and alkali, and insufficient alkali in some areas, resulted in incomplete digestion of aluminum fluoride. The final test results were lower than expected, with significant fluctuations between parallel samples, and a marked decrease in precision and accuracy. This demonstrates that layered packing and stepped heating are essential conditions for the alkali-soluble digestion of aluminum fluoride.
[0059] Comparative Example 4 The acidification pH in this comparative digestion method is inappropriate and there is no boric acid masking. The difference from Example 1 is that acid is added dropwise in step (5) to adjust pH≈7; the remaining steps are the same as in Example 1.
[0060] Test results:
[0061] The results showed that the RSD of the six parallel determinations in this comparative example was 1.89%, and the spiked recovery rate was 87.6%. Adjusting the solution to neutral caused aluminum ions to hydrolyze and precipitate, resulting in loss. Simultaneously, free fluoride ions were not complexed, forming stable fluoride-aluminum complexes that interfered with the ICP detection signal, leading to significantly lower results and large fluctuations in parallel samples. This demonstrates that pH control and fluoride ion masking are crucial for detection.
[0062] Comparative Example 5 The comparative digestion method does not use boric acid masking. The difference from Example 1 is that boric acid is not added in step (5) to complex free fluoride ions; the remaining steps are the same as in Example 1.
[0063] Test results:
[0064] The comparative example showed an RSD of 1.64% for six parallel determinations and a spiked recovery rate of 90.4%. Although the pH was controlled at 2-3 to avoid aluminum hydrolysis, the free fluoride ions in the system were not complexed, and fluoride-aluminum complexes were still generated, interfering with the instrument signal, resulting in lower test results and reduced precision. This indicates that adjusting the pH alone cannot eliminate fluoride interference; boric acid must be used to complex free fluoride to ensure accurate detection.
[0065] The comparison data between the above embodiments and comparative examples show that: 1. Layered packing and stepped heating calcination play a crucial role in controlling the digestion process: In Example 1, layered packing and stepped heating calcination were used. The RSD of six parallel measurements was only 0.62%, and the spiked recovery rate reached 98.6%, indicating complete digestion and stable results. In contrast, in Comparative Examples 1-3, layered packing, stepped heating, or both were omitted, respectively. All three examples exhibited localized sintering, splashing, and incomplete digestion, with spiked recoveries dropping to 81.2%–87.6%. These results were lower and showed significantly increased dispersion, indicating that layered packing and stepped heating calcination are necessary prerequisites for ensuring complete digestion of fluorinated aluminum inorganic materials and achieving high recovery rates and high precision.
[0066] 2. A significant synergistic effect exists between pH 2-3 acidification and boric acid masking: In Example 1, the leaching solution was acidified to pH 2-3 and sufficient boric acid was added, with an RSD of 0.62% and a spiked recovery rate of 98.6%. In Comparative Example 4, the solution was adjusted to neutral (pH≈7) without the addition of boric acid. Aluminum ions hydrolyzed to form flocculent aluminum hydroxide precipitate, resulting in loss. At the same time, free fluoride ions were not complexed to form fluorine-aluminum complexes, interfering with detection. The RSD increased to 1.89%, and the spiked recovery rate decreased to 87.6%. In Comparative Example 5, although pH was controlled at 2-3 to inhibit aluminum hydrolysis, boric acid was not added. Free fluoride ions still formed fluorine-aluminum complexes, interfering with the instrument signal. The RSD was 1.64%, and the spiked recovery rate was only 90.4%. The above data shows that controlling acidity alone cannot eliminate the spectral and matrix interference of fluoride ions. Acidification to pH 2-3 to stabilize the aluminum ion form and boric acid complexation to mask free fluoride ions must be carried out in tandem. Both are indispensable and work together to ensure the accuracy and precision of the detection results.
[0067] 3. Synergistic effect of the entire closed-loop process: In Example 1 with the full feature combination, the absence of any step in Comparative Examples 1-5 resulted in a decrease in spike recovery rate of more than 10 percentage points (as low as 81.2%) and a significant increase in RSD (as high as 9.31%). However, in Examples 1-4 with full feature synergy, even if the process parameters fluctuate within the claims range (Examples 3 and 4), the spike recovery rate is still ≥95.7% and the RSD is ≤0.84%, and it can be applied to different fluorinated aluminum materials such as cryolite without adjustment (Example 2). This shows that the technical features of the present invention are interconnected and mutually supportive. The absence of any step significantly deteriorates the detection effect, and the combination of features produces a systematic synergistic effect.
[0068] The test results of each embodiment and comparative example are summarized as follows:
[0069] This invention can also be implemented in various other ways. Without departing from the spirit and essence of this invention, those skilled in the art can make various corresponding changes and modifications according to this invention, but these corresponding changes and modifications should all fall within the protection scope of the appended claims.
Claims
1. A method for digesting fluorine-containing aluminum inorganic materials, characterized in that, Includes the following steps: (1) Sample pretreatment: The fluorinated aluminum inorganic material is dried to constant weight and cooled for later use; the fluorinated aluminum inorganic material is aluminum fluoride, cryolite, potassium fluoroaluminate or a mixture thereof; (2) Layered filling: Solid sodium hydroxide is laid at the bottom of the nickel crucible. The fluorinated aluminum inorganic material dried in step (1) is weighed and laid flat on top of the bottom layer of sodium hydroxide. The surface of the fluorinated aluminum inorganic material is covered with solid sodium hydroxide. The sodium hydroxide at the bottom of the nickel crucible accounts for 55% to 65% of the total sodium hydroxide mass. The total sodium hydroxide is the sum of the sodium hydroxide at the bottom of the nickel crucible and the sodium hydroxide covering the surface of the fluorinated aluminum inorganic material. The mass ratio of the fluorinated aluminum inorganic material to the total sodium hydroxide is 1:40 to 60. (3) Step heating and calcination: Place the filled nickel crucible into a muffle furnace, first heat it to 180~220℃ and calcinate it at a constant temperature for 8~12 minutes, then heat it to 530~570℃ and calcinate it at a constant temperature for 45~55 minutes; (4) Cooling leaching: After the calcination is completed, remove the nickel crucible and let it cool naturally to room temperature. Add hot water at 60~80℃ into the crucible and heat and stir at 80~100℃ until the melt is completely dissolved. (5) Acidification and fluorine masking: After the leaching and dissolution are completed, the solution is cooled to room temperature. First, hydrochloric acid or nitric acid is added dropwise to adjust the pH to 2-3. Then, boric acid is added to the solution so that the boric acid complexes the free fluoride ions released during the digestion of the fluorine-containing aluminum inorganic material under the pH conditions to obtain a digestion solution. The digestion is completed. The amount of boric acid added is 4-6g of boric acid per 0.1g of the fluorine-containing aluminum inorganic material.
2. The digestion method for fluorine-containing aluminum inorganic materials according to claim 1, characterized in that, In step (1), the drying conditions are to dry to constant weight at 100~110℃; in step (4), the mixture is heated and stirred on a hot plate at 80~100℃ until the molten material is completely dissolved.
3. The digestion method for fluorine-containing aluminum inorganic materials according to claim 1, characterized in that, The step-by-step heating and calcination in step (3) specifically includes: calcining at a constant temperature of 200℃ for 10 minutes, and then heating to 550℃ and calcining at a constant temperature for 50 minutes.
4. A method for detecting the aluminum content in fluorinated aluminum inorganic materials, characterized in that, The digestion method according to any one of claims 1 to 3 further includes the following steps: Step 1, First volume adjustment: Transfer all the digestion solution to the first volumetric flask, and make up to volume with pure water to obtain the first-stage mother liquor; Step 2, fractional dilution: Take the second volumetric flask and pre-add 0.5~2mL of hydrochloric acid or nitric acid to it, then transfer the first-stage mother liquor into it and dilute to the mark to obtain the test solution; Step 3: Preparation of standard curve: Using the matrix matching method, a sodium salt solution with a sodium ion concentration equivalent to that of the test solution is used as the matrix. The aluminum standard stock solution is diluted to prepare the aluminum standard working solution. An inductively coupled plasma atomic emission spectrometer is used to detect the characteristic emission line of aluminum at 396.1 nm. A standard curve is plotted with aluminum concentration as the abscissa and spectral intensity as the ordinate. Step 4, Sample Testing: Under the same instrument parameters and analytical spectral conditions as in Step 3, determine the intensity of the aluminum spectral line in the test solution, substitute it into the standard curve to calculate the concentration of aluminum in the test solution; combine the sample weight and the total dilution factor of the two stages to calculate the mass percentage of aluminum in the fluorine-containing aluminum inorganic material.
5. The method for detecting aluminum content in fluorinated aluminum inorganic materials according to claim 4, characterized in that, In step one, the first volumetric flask is a 500mL volumetric flask; in step two, the second volumetric flask is a 100mL volumetric flask.
6. The method for detecting aluminum content in fluorinated aluminum inorganic materials according to claim 4, characterized in that, In step two, the volume of primary mother liquor transferred is 0.5~2mL, and the ratio of the volume of pre-added hydrochloric acid or nitric acid to the volume of primary mother liquor transferred is 1:
1.
7. The method for detecting aluminum content in fluorinated aluminum inorganic materials according to claim 4, characterized in that, The aluminum concentration gradient of the aluminum standard working solution in step three is 0 μg / mL, 0.2 μg / mL, 0.8 μg / mL, and 1.4 μg / mL.
